Depression chains in seafloor of contrasting morphology, Atacama Trench margin: a comment on Marsh et al. (2018). Issue 3 (13th March 2019) - Purser, Autun; Herr, Helena; Dreutter, Simon; Dorschel, Boris; Glud, Ronnie N.; Hehemann, Laura; Hoge, Ulrich; Jamieson, Alan J.; Linley, Thomas D.; Stewart, Heather A.; Wenzhöfer, Frank
Abstract : This comment presents acoustic and visual data showing deep seafloor depression chains similar to those reported in Marsh et al. ( R. Soc. open sci. 5: 180286), though from a different deep-sea setting. Marsh et al. present data collected during cruise JC120 from polymetallic nodule rich sites within the Clarion-Clipperton Fracture Zone (CCFZ), at water depths of between 3999 and 4258 m. Within this comment, we present data collected with equivalent acoustic and imaging devices on-board the RV Sonne (SO261—March/April 2018) from the Atacama Trench, approximately 4000 m depth, which shows comparable depression chains in the seafloor. In contrast with the CCFZ observations, our study area was wholly free of polymetallic nodules, an observation therefore weakening the 'ballast collection' by deep-sea diving mammals formation hypothesis discussed in their paper . We support their alternate hypothesis that if these features are indeed generated by deep-diving megafauna, then they are more likely the resultant traces of infauna feeding or marks made during opportunistic capture of benthic fish/cephalopods. We observed these potential prey fauna with lander and towed camera systems during the cruise, with example images of these presented here. Both the SO261 and JC120 cruises employed high-resolution sidescan systems at deployment altitudes seldom used routinely until the last few years during scientific deep-sea surveys. Given that both cruises found these depression chains in contrasting physical regions of the East Pacific, they may have a more ubiquitous distribution than at just these sites. Thus, the impacts of cetacean foraging behaviour on deep seafloor communities, and the potential relevance of these prey sources to deep-diving species, should be considered.